Study on the Characteristics of Surface Contacted Friction According to ASTM of Different Lubricants - Tran, Duc Toan; Pham, Van Hung (Old Journal, 2019)
This paper presents the study on the characteristics of surface contacted friction according to ASTM of different commercial lubricants with the same viscosity index working at different temperature conditions. The results show that there are significant changes in the friction characteristics following the temperature of lubricants with equivalent viscosities. The changes in lubricant friction characteristics decide the wear resistant ability and longevity of the working friction pair. Therefore, choosing lubricant according to the viscosity index was not sufficient. It must also be based on the lubricant friction characteristic to ensure the longevity and reliability of the lubricated friction pair.